Pemberdayaan Petani Jamur Tiram Putih melalui Optimalisasi Teknologi Produksi dan Strategi Pemasaran Digital di Desa Tanjung Sari, Serang-Banten - Akbar, Taufik; Pranoto, Hadi; Sari, Alvita (Civiliza Publishing, 2025)
Agricultural development in Indonesia requires comprehensive approaches integrating farmer organizations, technological innovation, and marketing strategies to achieve food security and farmer welfare. The Kontak Tani Nelayan Andalan (KTNA) in Pabuaran Subdistrict, Serang Regency, has focused on oyster mushroom (Pleurotus ostreatus) cultivation as a strategic commodity. However, implementation faces significant challenges due to traditional methods, limited equipment, and inadequate marketing strategies. This community service program aims to support KTNA development through agribusiness-based economic empowerment in Tanjungsari Village by implementing appropriate technology and digital marketing capacity building. The program employed a participatory approach involving 38 KTNA members through five systematic stages: socialization, implementation, management, evaluation, and monitoring. Main interventions included introducing appropriate technology (media mixer and large-capacity steamer oven) and comprehensive digital marketing training. Implementation successfully transformed cultivation efficiency and productivity. The media mixer reduced mixing time by 50% (from over 3 hours to 1.5 hours for 100 bag logs) while improving media homogeneity. The steamer oven increased sterilization capacity to 400 bag logs per cycle, dramatically boosting productivity from 100 kg to 250-300 kg per cycle (150-200% improvement). Digital marketing training enhanced farmers' understanding of online marketing principles, social media utilization, marketplace platforms, and branding strategies. The program achieved 90% competency targets in production, business management, and marketing aspects. Results demonstrate that integrated appropriate technology and digital marketing training can significantly improve oyster mushroom cultivation sustainability, contributing to food security, farmer income enhancement, and agribusiness-based economic development.